A Quantitative Analysis for the Expression of AMP-Glu R2 Coding Gene in BALB/C Male Mice during Modafinil Administration - khudhair, Sura Razzaq (American Journal of Biology and Natural Sciences, 2026)
Nootropics often known as smart medicines, brain boosters, neuro-stimulants, behavioral stimulators, and intellect enhancers, are medications, nutrients, nutraceuticals, and food supplements that supposedly boost brain abilities like intellect, memory, intelligence, enthusiasm, focus, and concentration. The modafinil, including nootropics, is able to achieve amnesia restoration caused by, for example, scopolamine, electroconvulsive stimulation and hypotension. It was shown that modafinil modifies cognitive and behavioral processes and affects many brain proteins. Nevertheless, results were not identified at the stage of compact protein complex. In the nucleus accumbens, a critical part of brain’s reward systems, smart medicines including modafinil may modify the activity of AMPA-type glutamate receptor subunits. The effect of such a control on the general condition of inspiration is unknownIn the present study various concentrations of modafinil is administered to BALB/c male mice to check the expression levels of AMPA – Glu R2 sub units. Molecular and immunological approaches are utilized to check the final results of this study.